The Effect of a Proposed Volunteer Program on Developing Educational values for Eighth Grade Students - AlKhateeb , Fatima (Dirasat: Educational Sciences, 2021)
The study aims to identify the impact of a proposed voluntary program in developing some educational values. They include developing the concept of volunteering, helping others, love of work and productivity, sense of responsibility, cooperation and belonging, giving charity to science, leadership and organization, and spirit of competition. The program was designed according to exact rules and principles. The study was conducted on eighth grade students in the Northern Mazar District, Jordan. The study sample was selected from the total population of 705 students (males and females) distributed over 46 classes in the schools of the district. The research sample amounted to 40 female students divided into two groups: a control group of 20 students, and an experimental group of 20 students. The study finds that arithmetic averages and standard deviations of the level of educational values ​​(developing the concept of volunteering, helping others, love of work and productivity, sense of responsibility, cooperation and belonging, charity in science, leadership and organization, and spirit of competition) among eighth-grade students in the Northern Mazar District were moderate.